Study guides

Q: How to simplify 4 a-b plus 3 a-b?

Write your answer...

Submit

Related questions

5+4-3=6

When you simplify 49 plus 37 (49+37), the result is 86.

3+52+4 52+3=55+4 55+4=59

Gather like terms: 2m - m + 3 + 4 = m + 7.

Do the math. -4 -3 +6 = -7 + 6 = -1

Simply, you do this:3/4 + 3/4 =6/4Then you simplify it.

is eassy

ab + 4 + a + 4b factors to (a + 4)(b + 1)

Actually, I don't really think that you can simplify it, because if you convert them into fractions, there all over 1 and you can't simplify it. You can simplify it if it's: 5 plus 7 DIVIDED by 3. That was when you divide the 12 by 3 in fraction form, the 3 and one switch, and u can simplify 3 into 1 and 12 into four, so there by the answer is 4. (Sorry if confusing)

10 square root 3.

It is 14x+4 simplified

[(-4)(-3)]=-4•-3=-12 but since they're both negative the answer is positive so it's +12 + 6= 18

Factor out the 4. The answer is y-3/y+3

AB = 2 x 4 (8) C = 3 D = 5

3/24 + 4/24 = 7/24

8/9 + 3/9 + 2/9 = 13/9 = 1 4/9

x + 5 + 4 = x + 9

3 * x + 4 + 2xMDAS rule:3x + 4 + 2x5x + 4

Without parentheses, 3 x 4 = 12 2x + 12 factors to 2(x + 6)

To put a plus or minus sign with the digit 5

4^3√32-3^3√108+^3√256

4 cc

7g-10h

the answer to this question is : 3.8 = 38/10 then simplify it to 3 wholes and 8/10 ( 3 8/10) then if you want to simplify it to the final answer which is 3.8= 3 wholes and 4/5 (3 4/5) final answer 3.8 = 3 4/5

Factor it out: (x+2) squared